Pengaruh Disiplin Kerja, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Kinerja Pegawai Sekretariat Jenderal Dewan Perwakilan Daerah (DPD) Republik Indonesia - Dinda Sayyida Nafisa (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to determine the effect of variables of work discipline, work motivation, and job satisfaction on employee performance in the General Secretariat of the Regional Representative Council (DPD) of the Republic of Indonesia, both per and simultaneously. Data collection was carried out by distributing questionnaires, the study was conducted on 50 respondents, a sample of all employees of the General Secretariat of the Regional People's Representative Council (DPD) RI. Using the Likert scale, respondents' answers were processed by multiple regression analysis, t-test, f-test and test . The results showed that some work disciplines had a positive and significant effect on employee performance, work motivation had a positive and significant effect on employee performance and job satisfaction had a positive and insignificant effect on employee performance. Simultaneously, work discipline, work motivation, job satisfaction have a significant effect on the performance of employees of the General Secretariat of the Regional Representative Council (DPD) of the Republic of Indonesia.